Subspace Approach For Speech Signal Modelling And Classification - Tan, Alan Wee Chiat (2007)
Throughout the thesis, the proposed subspace classifiers are assessed on an isolated digit speech recognition problem. For purposes of comparison, the experiments also include two commonly used speech recognizers, i.e., the LPCC and MFCC recognizers.